Psychology in Hadith Perspective - Rahima Sikumbang Sarmadi (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Abstract : Allah Subhanahu Wata'ala created man from clay, Adam a.s and He created a wife for him from his body too, as stated in the Qur’anulkarim surah Annisa Verse 1. Then Allah Ta'ala gave pleasure to Adam and Hawa alaihimassalam. Unfortunately, behind the pleasure given by Allah Ta'ala, there are always eyes and souls that are jealous. He is the Devil Laknatullah, has an evil soul and always destroys good creatures by changing their behavior to evil. Since being expelled from heaven for their jealousy which becomes arrogance leads the devil swearing for being a seducer of the prophet Adam, his wife and their offspring until the doomsday. The enmity of good and bad souls has indeed existed since the time when humans were first created, even the children of Prophet Adam and Siti Hawa experienced the same thing. Habil and Qabil, with their jealousy of an arranged marriage, created the first bloodshed in the form of murder. This happens because of the demands of lust that come from the whispers of the devil to pollute the soul. The origin of the existence of good and bad souls, as stated in the Koran, that humans are always inspired by two things: good and evil, is the background of this research, more specifically how the soul is in the perspective of Nabawi's traditions. Finally, the writer can draw the conclusion that according to the hadith, the soul is the same thing as stated in the Koran. There is always a soul that tells its owner to do good and bad. It's just that, depending on the owner, want to follow the good or bad. It all depends on each other's faith.